@RealMe dan Dualitas Identitas Digital pada Remaja: Pengaruh Second Account sebagai Ruang Aman Ekspresi Diri di Media Sosial - Thohirah, Mursyidah Dianti; Nur, Haerani; Daud, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine how social media, especially second account users, influence the formation of adolescent self-identity in the digital era. Using the literature review method and the ex post facto correlational quantitative approach. The results of this study indicate that social media provide a flexible space for identity exploration, strengthen authentic self-expression, and build a supportive social community. The use of second accounts in particular provides an opportunity for adolescents to show a more honest side of themselves, regardless of the social pressures that often occur on the main account. However, this study also found negative risks such as social comparison, dependence on external validation, identity fragmentation, and the potential for mental health disorders. Reflective and authentic interactions on social media have been shown to encourage positive identity development, while passive interactions and focus on social image increase the risk of psychological problems. Therefore, collaboration is needed between adolescents, parents, educators, and digital service providers to facilitate healthier use of social media in shaping adolescent identity.